Sensitive liquid chromatography/tandem mass spectrometry method for the determination of two novel highly lipophilic anticancer drug candidates in rat plasma and tissues. (12th September 2017) - Hooshfar, Shirin; Linzey, Michael R.; Wu, Daqing; Gera, Lajos; Mamouni, Kenza; Li, Xin; Chen, Yanhua; Yang, Yang; Olorunyolemi, Oluwasegun; Bartlett, Michael G.
Abstract: A simple and sensitive liquid chromatography/electrospray ionization tandem mass spectrometry (LC‐ESI‐MS/MS) method was developed and validated for determination of two highly lipophilic anticancer drug candidates, LG1980 and GH501, in rat plasma and tissues (liver, kidney and femur bones). LG1980 and GH501 were extracted from rat plasma and tissue homogenates using liquid–liquid extraction. The method provided a linear range of 1.0–200.0 ng/mL for GH501 in plasma and LG1980 in plasma and liver. For both analytes in other tissue homogenates the linear range was 2.0–400.0 ng/mL. The method was validated with precision within 15% relative standard deviation, accuracy within 15% relative error and a consistent recovery. This method has been successfully applied in two preclinical studies for LG1980 and GH501 to determine their concentrations in rat plasma, liver, kidney and bone over 24 h after intravenous injection of compounds.